Using 3d Printed Magnetic Platform as Support for Screen Printed Electrode Applied for P-Toluenediamine Detection in Biological Fluid and Water Samples - Salazar-Gonzalez, R (Elsevier B.V., 2023)
The present work reports the development and application of a new electrochemical sensor for the determination of low concentration levels of p-toluenediamine (PTD) in biological fluids and surface water samples. The proposed sensor was developed using a 3D-printed magnetic device as platform for carbon screen printed electrode (CSPE) modified by magnetic nanoparticles functionalized with carboxylic groups and L-cysteine (MNP-CA-CYS). The results obtained from the morphological and electrochemical characterizations of the sensing platform enabled us to confirm the success of the sensor functionalization with L-cysteine and to have a better understanding of the electrochemical behavior and preconcentration of PTD on the electrode surface. PTD oxidation occurred at 0.24V on MNP-CA-CYS and the mechanism recorded an increase of 51.0% in anodic peak current. Under optimized conditions, the square wave voltammograms obtained for the electrode modified by 40.0 μL MNP-CA-CYS suspension at 1.0 mg mL−1, with accumulation time of 3 min, presented an analytical curve with linear range of 8.00 × 10−7 to 8.00 × 10−5 mol L−1, represented by the equation Iap = (0.383 ± 0.011)[PTD] - (8.112 ± 0.07) × 10−8 (R2 = 0.9994), and detection and quantification limits of 8.53 × 10−8 and 2.56 × 10−7 mol L−1, respectively. Finally, the proposed method was validated through comparison with high performance liquid chromatography coupled to diode array detector (HPLC-DAD) technique and was successfully applied for PTD determination in samples of surface water, tap water, fetal bovine serum and artificial urine. © 2022 Elsevier B.V.